Non-coding RNA-related antitumor mechanisms of marine-derived agents - Zhou, Zhixia; Cao, Qianqian; Diao, Yujing; Wang, Yin; Long, Linhai; Wang, Shoushi; Li, Peifeng (Frontiers in Pharmacology, 2022)
In the last two decades, natural active substances have attracted great attention in developing new antitumor drugs, especially in the marine environment. A series of marine-derived compounds or derivatives with potential antitumor effects have been discovered and developed, but their mechanisms of action are not well understood. Emerging studies have found that several tumor-related signaling pathways and molecules are involved in the antitumor mechanisms of marine-derived agents, including noncoding RNAs (ncRNAs). In this review, we provide an update on the regulation of marine-derived agents associated with ncRNAs on tumor cell proliferation, apoptosis, cell cycle, invasion, migration, drug sensitivity and resistance. Herein, we also describe recent advances in marine food-derived ncRNAs as antitumor agents that modulate cross-species gene expression. A better understanding of the antitumor mechanisms of marine-derived agents mediated, regulated, or sourced by ncRNAs will provide new biomarkers or targets for potential antitumor drugs from preclinical discovery and development to clinical application.